Neoumbilicoplasty with vertical island pedicle flap for a large pigmented umbilical nevus - Karel Borroto Martínez; Kárel Durán Marrero; Juan Carlos Muñiz Vigueras; Yoanna Ramírez Fernández (Revista Cubana de Medicina Militar)
Introduction: The umbilicus is a unique physiologic scar of human body. Its absence leads to an unnatural abdominal appearance and can cause psychological and social complexes. Objective: To present a case of neoumbilicoplasty with vertical island pedicle flap for a large pigmented umbilical nevus. Clinical case: A healthy 50-year-old female patient with a history of a pigmentated nevus on the umbilicus since childhood that complains of changes in size and color of it. She also referred notice a lump in the upper umbilical region which was an umbilical hernia. The patient underwent an omphalectomy with oncological margins, an umbilical hernia repair and a neoumbilicoplasty with vertical island pedicle flap. Seroma was the only postoperative complication. Aesthetic results were acceptable and satisfied the patient. Conclusions: This is a rare case not only because the umbilical skin lesions are uncommon but the neoumbilicoplasty technique is rarely used.